Advances in solid catalysts for selective hydrogenolysis of glycerol to 1,3-propanediol - Bhowmik, Susmita; Darbha, Srinivas (Catalysis Reviews-Science and Engineering, 2021)
Glycerol is one of the top 12 platform chemicals obtained from biomass. Its surplus availability as a by-product of biodiesel, fat-splitting and soap manufacturing industries and affordable price lends significant opportunity for its valorization, using solid catalysts, into propanediols (PDOs), particularly to 1,3-propanediol (1,3-PDO), by selective hydrogenolysis. 1,3-PDO is an important chemical with wide applications including that as a precursor in polymers manufacturing. However, the synthesis of 1,3-PDO by selective cleavage of the secondary C-O bond of glycerol in the presence of hydrogen (instead of the primary C-O bond yielding 1,2-PDO) is highly challenging. Of late, supported Pt and Ir catalysts in combination with a reducible oxide (WO(x)or ReOx) were found selective for 1,3-PDO formation. Support, metals composition and additives (co-added metals) affect the performance of these catalysts. Detailed investigations revealed that metal dispersion, electronic connectivity between metal and metal oxide/support, hydrogen activation/spillover and Bronsted acidity are some parameters that influence the activity and selectivity of these bi-functional, metal-metal oxide catalysts. This review summarizes the latest advances in these solid catalysts for selective hydrogenolysis of glycerol to 1,3-PDO, a monomer for advanced polymers.
Keywords: 1; 3-Propanediol; bifunctional metal-metal oxide catalyst; biomass valorization; Glycerol; Hydrogenolysis

Advances in catalytic conversion of lignocellulosic biomass to ethylene glycol - Enjamuri, Nagasuresh; Darbha, Srinivas (Catalysis Reviews-Science and Engineering, 2024)
Ethylene glycol (EG) is an industrial chemical with multiple applications in polymers, anti-freeze agents, coolants, desiccants and de-icing fluids. It is prepared mainly from fossil feedstock resources. However, its manufacture from renewable sources like lignocellulosic biomass is attractive from the view points of carbon-neutrality and environmental benefits. A few industries have already ventured or committed to produce biomass-derived EG (bio-EG) on a pilot to demonstration scale. At present bio-EG is more expensive than the EG made from fossil resources. Advances are happening in developing more efficient and selective catalysts for the direct conversion of raw biomass and its hydrolysis products (cellulose and glucose) into bio-EG. This review presents the recent advances in catalysts for producing bio-EG.
Keywords: 2-diol; biomass to chemicals; ethane-1; Hydrogenolysis; Lignocellulose; Monoethylene glycol; solid catalyst